Complementary redescription of Raja lintea Fries, 1839 (Elasmobranchii, Rajidae) and its revised generic assignment - Stehmann, Matthias F. W. (Zootaxa, 2012)
The generic status of many skate species has been revised during the past six decades by various authors having introducednew diagnostic morphological and anatomical characters. As a consequence, the original family Rajidae and its very di-verse type genus Raja Linnaeus, 1758 have been split into several families, subfamilies, genera and subgenera which werein several cases provisionally established due to the lack of specific material required. However, quite a number of speciesoriginally in Raja remained incompletely studied and still assigned to Raja sensu lato, because, e.g., mature males werenot yet available for studies of their relevant clasper features. One of these species is the northern North Atlantic Rajalintea Fries, 1839 which Stehmann (1970, 1973) and Stehmann and Bürkel (1984) could not assign definitively to the up-dated diagnosis of any revised rajid genus, because a mature male was not available. McEachran and Miyake (1990) andMcEachran and Dunn (1998) reallocated Raja lintea to the subgenus/genus Dipturus Rafinesque, 1810, respectively, with-out evidence or explanation given.Since a mature male of R. lintea became available, the author has reinvestigated the species, presents here its so farunknown diagnostic characters of clasper morphology and skeleton, scapulocoracoid and pelvis, and assigns the species on this basis to the genus Rajella Stehmann, 1970.